Irrational exuberance: An evolutionary perspective on the underlying causes of the financial crisis - Andy Hira (Intereconomics, 2013)
In the years leading up to the crisis, there were a number of warning signs that signalled a breakdown of basic fiduciary soundness. The following article addresses the problem of inattention to those warning signs and calls into question the commonly proposed causes of the crisis. This paper suggests that the more intangible aspects of human nature revealed by the crisis are the key to unlocking the paradoxical self-destructive behaviour behind it and thus the types of remedies that need to be considered.
Keywords: 330